Implications of Applying the International Financial Reporting Standards (IFRSs) for Small and Medium-Sized Enterprises on the Accounting Environment in Jordan - Walid Zakaria Siam; Muhammed Yassien Rahahleh (Journal of Accounting, Business and Management (JABM), 2010)
This study aims at identifying the implications of applying the International Financial Reporting Standards (IFRSs) for small and medium-sized enterprises (SMEs) in Jordan, the accountants' advocacy in SMEs of the application of these standards, and the barriers (difficulties) limiting such application. To achieve the study objectives, the researcher designed and distributed a questionnaire to the accountants who manage the financial activities and the accounting records in the study sample represented by the enterprises listed and classified as SMEs at the beginning of 2008. Upon analyzing the responses to the questionnaires, the following results were concluded, including: an increase in accountants' advocacy in SMEs in Jordan of the application of IFRSs in these enterprises, and their conviction of the positive implications to be achieved in case of applying of such standards, emphasizing that there are barriers (difficulties) limiting the application of these standards.